Matemágica em sala de aula: uma proposta lúdica usando a resolução de problemas - Almeida, Vagner Lopes de (2017)
This work aims to awake interest in the study of mathematics and contribute to the improvement of learning in mathematics. We use the steps of problem solving of Polya and the ludic one as a tool to motivate the taste for mathematics. These tools can improve student participation and the students’ achievement in the classroom, stimulate mathematical reasoning, creativity, ability to solve problems, develop concentration and socialization, increasing the individual’s interactions with the other people. We select and describe a magic list, where we detail the contents and abilities predominant in each magic, showing the math behind each trick. In addition to logical reasoning, we basically use only the knowledge of basic algebra and arithmetic to justify every trick. By revealing the secret of each magic it is easy to see that we can work various mathematical contents that can aid learning.